Basic physical geology - Robinsons, Edwin Simons (New York : Wiley, 1982)
This textbook is concerned with how the earth works and how it is put together.
Section one. Introduction to the earth -- Section Two. The earth's size, shape, and interior zones -- Section Three. The rocks of the earth -- Section Four. The face of the earth -- Section five. Other planets.
Includes index.
Keywords: PHYSICAL GEOLOGY